2021
DOI: 10.3802/jgo.2021.32.e10
|View full text |Cite
|
Sign up to set email alerts
|

Total laparoscopic vs. conventional open abdominal nerve-sparing radical hysterectomy: clinical, surgical, oncological and functional outcomes in 301 patients with cervical cancer

Abstract: Objective: Total laparoscopic nerve-sparing radical hysterectomy (TL-NSRH) has been considered a promising approach, however, surgical, clinical, oncological and functional outcomes have not been systematically addressed. We present a large retrospective multicenter experience comparing TL-NSRH vs. open abdominal NSRH (OA-NSRH) for early and locally-advanced cervical cancer, with particular emphasis on post-surgical pelvic function. Methods: All consecutive patients who underwent class C1-NSRH plus bilateral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…In addition, compared to a recent study on NSRH using laparoscopy and laparotomy, our data showed improvement in terms of duration of surgery and blood loss, indicating that the surgical procedure used in our study is less invasive to patients 11 …”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In addition, compared to a recent study on NSRH using laparoscopy and laparotomy, our data showed improvement in terms of duration of surgery and blood loss, indicating that the surgical procedure used in our study is less invasive to patients 11 …”
Section: Discussionsupporting
confidence: 55%
“…In addition, compared to a recent study on NSRH using laparoscopy and laparotomy, our data showed improvement in terms of duration of surgery and blood loss, indicating that the surgical procedure used in our study is less invasive to patients. 11 In recent years, the development of minimally invasive surgery (MIS) has progressed, and laparoscopic surgery and robotic surgery have become more common. There have also been several reports on minimizing the invasiveness of nerve-sparing methods.…”
Section: Discussionmentioning
confidence: 99%
“…However, owing to the difference in the advancement of medical and healthcare facilities across the world, there is a deviation in clinical staging before surgery, an imbalance in the radiotherapy resources, limitations of regional-related medical conditions, and the subjective choice made by patients, considering that a considerable number of patients continue to opt for surgical resection as an initial treatment ( 33 35 ). In recent years, with the development of the minimally invasive concept, surgical instruments, and relevant technology, laparoscopic RH for cervical cancer has been proved to be safe and effective, thereby gradually replacing the traditional open surgery approach ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the LACC trial did not demonstrate a significant quality-of-life benefit from a laparoscopic procedure, other studies suggest reduced complication rates, shorter hospital stays and lower costs [15,[26][27][28][29]. The question arises whether laparoscopic radical hysterectomy is a medically justifiable procedure in certain cases.…”
Section: Discussionmentioning
confidence: 99%